IMPLEMENTASI KEBIJAKAN TENTANG PENGELOLAAN BADAN USAHA MILIK DESA LAGADING KABUPATEN SIDENRENG RAPPANG - Wahyudding Muhlis; Sahar Sahar (JIA: Jurnal Ilmiah Administrasi, 2021)
The purpose of this study is to determine the implementation of village regulations Lagading No. 4 of 2014 on the management of village-owned enterprises In the village Lagading District of Pitu Riase Sidenreng Rappang and Factors Affecting Implementation of Village Regulations Lagading No. 4 of 2014 on the management of village-owned enterprises In the village Lagading Pitu subdistrict Riase Sidenreng Rappang. The village population of 36 board BUMDesa Lagading. The sample in this research is the whole of the population that is 36 BUMDesa board, based on the engineering sample is saturated. This type of research is quantitative descriptive with basic research, survey research and the type of data in this research is quantitative research, sources of data in this study are primary data and secondary data. Data collection techniques used in this research is observation, interviews, questionnaires,were used that frequency tabulation analysis and simple regression analysis with SPSS 16.0 for Windows. Results of Implementation Lagading Village Regulations No. 4 of 2014 on the management of village-owned enterprises in the Village District of Pitu Riase Lagading Sidenreng Rappang are in the category of "no good" with a percentage of 46.8%, it can be said that there is significant influence between the Implementation Regulations Lagading Village No. 4 of 2014 on the management of village-owned enterprises in the village Lagading District of Pitu Riase Sidenreng Rappang, it is evident from the results of statistical analysis using multiple linear regression, the obtained t count = 2,621> t table 1.688 with a significance value 0,000 <0 , 05, and factors Affecting Implementation Lagading Village Regulations No. 4 of 2014 on the management of village-owned enterprises in the Village District of Pitu Riase Lagading Sidenreng Rappang namely environmental conditions, 80.4% are in the category of "good" while 42.6% inter-organizational relationships, 48.8% of resources, characteristics and capabilities of 56%. the category of "unfavorable".